2003
DOI: 10.1046/j.1432-1033.2003.03630.x
|View full text |Cite
|
Sign up to set email alerts
|

AtCYS1, a cystatin from Arabidopsis thaliana, suppresses hypersensitive cell death

Abstract: In plants, cysteine protease inhibitors are involved in the regulation of protein turnover and play an important role in resistance against insects and pathogens. AtCYS1 from Arabidopsis thaliana encodes a protein of 102 amino acids that contains the conserved motif of cysteine protease inhibitors belonging to the cystatin superfamily (GlnVal-Val-Ala-Gly). Recombinant A. thaliana cystatin-1 (AtCYS1) was expressed in Escherichia coli and purified. AtCYS1 inhibits the catalytic activity of papain (K d ¼ 4.0 · 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
143
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(148 citation statements)
references
References 76 publications
(104 reference statements)
2
143
0
3
Order By: Relevance
“…Several transgenic plant lines expressing exogenous cystatins were successfully produced over the last 15 years (e.g. Masoud et al, 1993;Benchekroun et al, 1995;Leplé et al, 1995;GutierrezCampos et al, 1999;Van der Vyver et al, 2003;Outchkourov et al, 2004), but recent studies reported pleiotropic effects of these proteins affecting major biological processes such as flowering, programmed cell death, tolerance to biotic stresses, and defense protein induction (Gutierrez-Campos et al, 2001;Belenghi et al, 2003;Van der Vyver et al, 2003;Rojo et al, 2004;Vaillancourt, 2005). Little is still known about the exact regulatory functions of Cys proteases in plant cells, but their obvious importance at the genome level (Beers et al, 2004) and their broad distribution in plant tissues and cells (Grudkowska and Zagdanska, 2004;Schaller, 2004) suggest a significant role for these enzymes in various cellular and developmental processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several transgenic plant lines expressing exogenous cystatins were successfully produced over the last 15 years (e.g. Masoud et al, 1993;Benchekroun et al, 1995;Leplé et al, 1995;GutierrezCampos et al, 1999;Van der Vyver et al, 2003;Outchkourov et al, 2004), but recent studies reported pleiotropic effects of these proteins affecting major biological processes such as flowering, programmed cell death, tolerance to biotic stresses, and defense protein induction (Gutierrez-Campos et al, 2001;Belenghi et al, 2003;Van der Vyver et al, 2003;Rojo et al, 2004;Vaillancourt, 2005). Little is still known about the exact regulatory functions of Cys proteases in plant cells, but their obvious importance at the genome level (Beers et al, 2004) and their broad distribution in plant tissues and cells (Grudkowska and Zagdanska, 2004;Schaller, 2004) suggest a significant role for these enzymes in various cellular and developmental processes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies used protein engineering approaches to improve the effectiveness of protease inhibitors toward herbivorous insect or nematode proteases (Urwin et al, 1995;Inanaga et al, 2001;Koiwa et al, 2001;Ceci et al, 2003;Martinez et al, 2003;Melo et al, 2003), but little attention has been paid to the impact of such modifications in a multitrophic context. The ability of recombinant plant cystatins to alter digestive protease activities in insect predatory arthropods via their herbivorous prey fed the modified plant has been documented in recent years (Bouchard et al, 2003a(Bouchard et al, , 2003bFerry et al, 2003;Alvarez-Alfageme et al, 2007), as well as some unintended pleiotropic effects of these inhibitors in planta significantly altering developmental processes and stress responses in the modified plant (Gutierrez-Campos et al, 2001;Belenghi et al, 2003;Van der Vyver et al, 2003;Vaillancourt, 2005). Using a collection of 29 cystatin variants derived from the eighth inhibitory unit of tomato (Solanum lycopersicum) multicystatin, SlCYS8 (formerly LeCYS8; Girard et al, 2007), we assessed here the usefulness of site-directed mutagenesis at hypervariable (positively selected) amino acid sites for the improvement of both the inhibitory potency and specificity of plant cystatins toward herbivorous insect digestive Cys proteases.…”
mentioning
confidence: 99%
“…Until now, PhyCys have been shown to have a role in plant growth and development, senescence, and programmed cell death (Solomon et al, 1999;Corre-Menguy et al, 2002;Belenghi et al, 2003;Kiyosaki et al, 2007;Weeda et al, 2009). However, these studies involved individual cystatin members from multiple plant species.…”
Section: ([Lvi]-[agt]-[rke]-[fy]-[as]-[vi]-x-[edqv]-mentioning
confidence: 99%
“…It is known that NO and H 2 O 2 can also chemically react to produce singlet oxygen or hydroxyl radicals and that these species can cause cell death. However, overexpression of a Cys protease inhibitor in Arabidopsis cell suspensions and tobacco plants suppresses NO-ROS-mediated cell death, providing evidence that cells die through the stimulation of an active process involving Cys proteases (Belenghi et al, 2003).…”
Section: No-ros Cooperation During the Hrmentioning
confidence: 99%